Pengembangan Aplikasi Notulensi Rapat Berbasis Web Pada Rumah Sakit Menggunakan Motode Waterfall - Febri, Febri; Wardani, Muhammad; Astri, Lola Yorita; Surya, Chandy Ophelia; Rofi'i, Imam (Journal of Information System Research (JOSH), 2026)
Baiturrahim Hospital in Jambi routinely holds coordination and evaluation meetings as part of its efforts to improve the quality of hospital services and management. However, the process of recording meeting minutes is still done manually using separate documents, resulting in delays in report preparation, difficulties in searching meeting archives, and an increased risk of data loss. This study aims to develop a web-based meeting minutes application that can support the process of recording, storing, and presenting meeting reports in an integrated manner. The software development method used is the Waterfall method, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. Data collection was carried out through workflow observations and interviews with administrative staff and related units at Baiturrahim Hospital in Jambi. The results of functional testing indicate that the application can accelerate the process of creating meeting minutes, improve the ease of searching and managing meeting archives, and assist in monitoring the follow-up of meeting results in a more structured manner. Thus, this web-based meeting minutes application is considered suitable for use as a supporting tool for meeting administration and has the potential to increase the effectiveness and efficiency of meeting management at Baiturrahim Hospital in Jambi.